2019
DOI: 10.18823/asiatefl.2019.16.1.15.235
|View full text |Cite
|
Sign up to set email alerts
|

Identity Development of Korean Writing Tutors of English : Working on the Border

Abstract: This study examines the identity development of Korean graduate students who worked as tutors of English writing at a Korean university, outside of the context of a writing studio. While many studies have been conducted to better understand the experiences of writing tutors at writing centers, several scholars have emphasized the importance of examining the identity construction of writing tutors who work outside writing centers. They argue that these tutors have more flexibility in developing their own identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…For example, after examining Korean tutors' interactions with their Korean tutees, Kim (2014, 2017) found that, for the purpose of helping the tutees to understand feedback as well as to identify solutions on their own, the tutors often referred to direct translation from L1 to L2 or vice versa, which is a strategy utilized only among tutors and tutees who share the same native language background. Cho (2019), in a study examining Korean writing tutors' identity development, implied that NNS tutors have developed peculiar identities as writing tutors: they feel like they are straddling a border, as they identify themselves neither as writing instructors nor as native speakers of English. Their insecurity was represented in their written feedback: they preferred indirect feedback and hedged comments because of their lack of confidence as tutors who had no experience of tutoring writing.…”
Section: Strategies Used By Non-native Speaker Tutorsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, after examining Korean tutors' interactions with their Korean tutees, Kim (2014, 2017) found that, for the purpose of helping the tutees to understand feedback as well as to identify solutions on their own, the tutors often referred to direct translation from L1 to L2 or vice versa, which is a strategy utilized only among tutors and tutees who share the same native language background. Cho (2019), in a study examining Korean writing tutors' identity development, implied that NNS tutors have developed peculiar identities as writing tutors: they feel like they are straddling a border, as they identify themselves neither as writing instructors nor as native speakers of English. Their insecurity was represented in their written feedback: they preferred indirect feedback and hedged comments because of their lack of confidence as tutors who had no experience of tutoring writing.…”
Section: Strategies Used By Non-native Speaker Tutorsmentioning
confidence: 99%
“…Their insecurity was represented in their written feedback: they preferred indirect feedback and hedged comments because of their lack of confidence as tutors who had no experience of tutoring writing. Cho (2019) only investigated their written feedback, but their interactions with tutees are also worth exploring to see whether their peculiar identities as NNS tutors may lead them to use specific strategies while working with their tutees. To add to this understanding, this study explores what strategies NNS tutors use during their tutorials and how their use of a certain strategy relates to their identities as writing tutors.…”
Section: Strategies Used By Non-native Speaker Tutorsmentioning
confidence: 99%